БАГАТОШАРОВІ ІНДУКТОРИ ДЛЯ УСТАНОВКИ ІНДУКЦІЙНОЇ ТЕРМООБРОБКИ АЛЮМІНІЄВИХ ЗЛИВКІВ ПРИ ПРЕСУВАННІ КАТАНКИ ДЛЯ СИЛОВИХ КАБЕЛІВ - Жаркін, А.Ф.; Гориславець, Ю.М.; Глухенький, O.I.; Білянін, Р.В. (Інститут електродинаміки Національної академії наук України, 2024)
On the basis of the developed mathematical model, computer (numerical) modeling of electrothermal processes in a multi-layer inductor installation, which is used for heating cylindrical aluminum ingots (blanks) before pressing the wire rod, as a basis for obtaining current-conducting cores of power cables from it, was carried out. Single-phase and three-phase multilayer inductors of the galette type were studied, as a result of which it was shown that the maximum value of the electrical efficiency of such an installation for both inductors is provided by their three-layer winding with a water-cooled copper tube of rectangular section. For both inductors, distributions along the radius and length of the aluminum blanks of the volumetric specific power and the specific linear power of heat release from the eddy currents induced in the blanks were obtained. For a three-phase inductor, such distributions were obtained when feeding it with voltages with phase shift angles of 120 and 60 degrees. The losses in the turns of the inductors and their distribution along the length and layers of both inductors were also studied. References 8, tables 2, figures 7.